Comparative analysis of percutaneous revascularization practice in the United States and the United Kingdom: Insights from the BMC2 and BCIS databases. Issue 3 (9th February 2023) - Wanamaker, Brett L.; Shoaib, Ahmad; Seth, Milan; Sukul, Devraj; Mamas, Mamas A.; Gurm, Hitinder S.
Abstract: Background: International registry comparisons provide insight into regional differences in clinical practice patterns, procedural outcomes, and general trends in population health and resource utilization in percutaneous coronary intervention (PCI). We sought to compare data from a state‐wide PCI registry in the United States with a national registry from the United Kingdom (UK). Methods: We analyzed all PCI cases from the Blue Cross Blue Shield of Michigan Cardiovascular Consortium and the British Cardiovascular Intervention Society registries from 2010 to 2017. Procedural characteristics and in‐hospital outcomes were stratified by PCI indication. Results: A total of 248, 283 cases were performed in Michigan and 773, 083 in the United Kingdom during the study period. The proportion of patients with a prior diagnosis of diabetes in Michigan was nearly double that in the United Kingdom (38.9% vs. 21.0%). PCI for ST‐elevation myocardial infarction was more frequent in the UK (25% UK vs. 14.3% Michigan). Radial access increased in both registries, reaching 86.8% in the United Kingdom versus 45.1% in Michigan during the final study year. Mechanical support utilization was divergent, falling to 0.9% of cases in the United Kingdom and rising to 3.95% of cases in Michigan in 2017. Unadjusted crude mortality rates were similar in the two cohorts, with higher rates of post‐PCI transfusion and other complications in the Michigan population. Conclusions: In a real‐world comparison using PCI registries from the US and UK, notable findings include marked differences in the prevalence of diabetes and other comorbidities, a greater proportion of primary PCI with more robust adoption of transradial PCI in the United Kingdom, and divergent trends in mechanical support with increasing use in Michigan.